PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI DAN KINERJA KARYAWAN - Yandono, Prayuda Eri; Rahayu, Yayuk Ngesti (Manajemen & Bisnis Jurnal, 2016)
Abstract, Purpose analyzing the direct and indirect effects of leadership style and organizational culture on organizational commitment and employee performance. In addition, this study also analyzes the effect of indirect style butterfly. The population of this research is all employees of sugar factory Tjoekir Jombang as many as 262 people to sample as many as 157 people. Analysis of the data used in the study using path analysis. The results showed that the leadership style and organizational culture directly affect organizational commitment, leadership styles, organizational culture and organizational commitment directly affect employee performance, organizational commitment capable of mediating influence between leadership style and organizational culture on employee performance. Keywords: leadership style, Cultural Studies organization, organizational commitment and employee performance